2011
DOI: 10.1063/1.3607976
|View full text |Cite|
|
Sign up to set email alerts
|

Improved carrier concentration control in Zn-doped Ca5Al2Sb6

Abstract: Ca 5 Al 2 Sb 6 is an inexpensive, Earth-abundant compound that exhibits promising thermoelectric efficiency at temperatures suitable for waste heat recovery. Inspired by our previous study of p-type Ca 5Àx Na x Al 2 Sb 6 , this work investigates doping with Zn 2þ on the Al 3þ site (Ca 5 Al 2Àx Zn x Sb 6 ). We find Zn to be an effective p-type dopant, in contrast to the low solubility limit and poor doping efficiency of Na. Seebeck coefficient measurements indicate that the hole band mass is unaffected by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 32 publications
3
38
0
1
Order By: Relevance
“…Sb 6 , in which the substitution of Zn 2+ on the Al 3+ site leads to an increase in carrier concentration by two orders of magnitude and a clear transition from nondegenerate to degenerate semiconducting behavior. 28 Structural differences between the A 5 Al 2 Sb 6 phases, in addition to the possible influence of the cation on the stability of acceptor defects (e.g., Sr vacancies and Zn substitution on Al site), could explain this disparity. In previous studies, Na 1+ on the Ca 2+ site was a successful dopant in both Ca 5 Al 2 Sb 6 and Ca 3 AlSb 3 compounds, 16,18 suggesting that similar substitutions may prove successful in increasing the carrier concentration in Sr 5 Al 2 Sb 6 .…”
Section: Electronic Transportmentioning
confidence: 99%
“…Sb 6 , in which the substitution of Zn 2+ on the Al 3+ site leads to an increase in carrier concentration by two orders of magnitude and a clear transition from nondegenerate to degenerate semiconducting behavior. 28 Structural differences between the A 5 Al 2 Sb 6 phases, in addition to the possible influence of the cation on the stability of acceptor defects (e.g., Sr vacancies and Zn substitution on Al site), could explain this disparity. In previous studies, Na 1+ on the Ca 2+ site was a successful dopant in both Ca 5 Al 2 Sb 6 and Ca 3 AlSb 3 compounds, 16,18 suggesting that similar substitutions may prove successful in increasing the carrier concentration in Sr 5 Al 2 Sb 6 .…”
Section: Electronic Transportmentioning
confidence: 99%
“…The main factor determining drift velocity is scattering time. The most important sources of scattering in typical semiconductor materials include (a) boundary scattering from pores or grain boundaries, (b) activation barrier at grain boundaries, (c) local strain field, or (d) ionized impurity scattering [19]. Sanyal et al [20] investigated the electrical conductivity and Hall mobility measurements on CIS films and observed that scattering at the grain boundaries is a predominant factor in controlling the electron transport properties at low temperatures.…”
Section: Resultsmentioning
confidence: 98%
“…This model provides a reasonable lowest j phonon value in disordered materials, 24 amorphous, 25 and structurally complex solids such as Zintl-phases 26 and icosahedral quasicrystals 27 . The calculated j min over 300 K for the RuGa 2 is almost the constant value of 1.0 W m À1 K À1 .…”
Section: Samplementioning
confidence: 96%